ANALISIS KONTRIBUSI PAJAK DAN RETRIBUSI DAERAH PADA PENDAPATAN ASLI DAERAH DI DINAS PENDAPATAN ASLI KOTA MAKASSAR - Rianthy, Gina Anggi (IJMA (Indonesian Journal of Management and Accounting), 2024)
This study aims to determine the development of the contribution of local taxes and regional levies to the local revenue of Makassar City. In this study, data were obtained through observation, documentation, and literature study. The population includes all reports on the realization of the budget, reports on the realization of regional levies and regional taxes for the City of Makassar, and as a sample, reports on the realization of regional income and budget reports for 2020-2023. Meanwhile, the analytical method used is the contribution of PAD, namely Regional Taxes and Levies. The results of this study indicate that the contribution of Regional Tax Revenue and Regional Levies to regional original revenues often fluctuates or is not constant from 2020-2023. Based on the contribution of local taxes and regional levies to regional original income, it has fluctuated or not been constant in the last three years (2020-2023) where the lowest contribution of local taxes to PAD in 2022 is 99.36% and the highest contribution of regional taxes to PAD in 2021 of 99.49% while regional levies have increased in 2022 by 63.97% from the previous year. So, it can be concluded that regional tax revenues and regional levies have increased depending on Regional Original Revenue, which can be concluded that the contribution of regional taxes and regional levies depends on Makassar City Regional Original Revenue.